Diagnostic Devices for Isothermal Nucleic Acid Amplification - Chia-Chen Chang; Chien-Cheng Chen; Shih-Chung Wei; Hui-Hsin Lu; Yang-Hung Liang; Chii-Wann Lin (Sensors, 2012)
Since the development of the polymerase chain reaction (PCR) technique, genomic information has been retrievable from lesser amounts of DNA than previously possible. PCR-based amplifications require high-precision instruments to perform temperature cycling reactions; further, they are cumbersome for routine clinical use. However, the use of isothermal approaches can eliminate many complications associated with thermocycling. The application of diagnostic devices for isothermal DNA amplification has recently been studied extensively. In this paper, we describe the basic concepts of several isothermal amplification approaches and review recent progress in diagnostic device development.